Pelatihan Microsoft PowerPoint untuk Meningkatkan Keterampilan Aplikasi Komputer pada Guru Sekolah Dasar di kecamatan Mutiara Timur - Beureunun Kabupaten Pidie - Win, Konadi; Abqa, Rizkan; Yanna, Sri; Purnamasari, Purnamasari (Aceh Journal of Community Engagement (AJCE), 2024)
The development of information technology today, especially software, helps teachers in particular and in the world of education in general. So educators are required to be able to master information technology software, such as Microsoft PowerPoint. PowerPoint can be used as a medium, which has many features such as creating more dynamic presentation slides and publications with the use of interactive media. This community service activity provides training on the use of the Microsoft PowerPoint application as interactive media to increase the creativity of teaching teachers in elementary schools in Mutiara Timur Beureunun sub-district, Pidie Regency. It is hoped that this training will provide direct benefits for teachers in the form of knowledge, information and Microsoft PowerPoint application skills. As a result of the training, the participants know and can use the tools or features in this application, such as text art, image import, animation import, video import and others that will make the slides look attractive. This community service activity can generally be said to be beneficial for the participants considering that not all of the previous participants understood and had not utilized this media for the learning or teaching and learning process